2002
DOI: 10.1023/a:1020401122858
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A structural equation model (SEM) examined interrelationships among psychosocial variables known to affect the health and development of well siblings and parents when a child with a chronic illness or disability is a member of the family. Using dyads of 252 well children and parents, socioeconomic status (SES) and family cohesion were associated with the parent-reported behavior of the well sibling. SES also influenced the mood of the mother that in turn influenced family cohesion. The well sibling's knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Approximately 4,500 pregnancies every year in Europe result in a baby or foetus affected by an NTD, and in the USA, 2,500 live births are affected by NTDs each year [51]. In China, 100,000 infants are born annually with NTDs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 4,500 pregnancies every year in Europe result in a baby or foetus affected by an NTD, and in the USA, 2,500 live births are affected by NTDs each year [51]. In China, 100,000 infants are born annually with NTDs [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of decline has not been as dramatic as expected [ 25 – 29 ] and despite measures to reduce NTDs, approximately 4,500 pregnancies every year in Europe result in a live birth, stillbirth, or termination where a baby or fetus has been affected by an NTD [ 29 ], and in the US there are 2,500 live births of children with NTDs each year [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…An integrative review that synthesized studies about sibling adjustment to childhood chronic illness identified how siblings learned knowledge about the illness from their parents (Lummer-Aikey & Goldstein, 2021). While siblings expressed wanting to learn more information about the illness of their sibling, parents may decide how much information to share based on the age of the siblings and the type of diagnosis (Lummer-Aikey & Goldstein, 2021;Plumridge et al, 2011;Williams et al, 2002). Sibling participants further described how their mothers often provided information and resolved conflicts in the sibling relationship.…”
Section: Discussionmentioning
confidence: 99%